A Molecular Dynamics Simulation Study on the Initial Stage of Si(001) Oxidation Under Biaxial Strain - Cao, Haining; Pamungkas, Mauludi Ariesto; Kim, Byung-Hyun; Lee, Kwang-Ryeol (AMER SCIENTIFIC PUBLISHERS, 2013)
We have studied the very early stage of the room temperature oxidation of the externally-strained Si(001) surface using molecular dynamics simulation. It was found that the different treatment history of the sample under the same strain resulted in the difference in the number density of dimer. The as-prepared samples of different treatment history with 12.15% strain were used to investigate the initial oxidation behavior of Si(001). 500 times of independent deposition of single oxygen molecule onto the random position of clean Si(001) surface was simulated. Oxidation behavior was statistically analyzed for various dimer density of the surface which is dependent on strain-treatment history. Oxygen uptake and penetration depth profile showed an important role of dimers on the surface oxidation behavior.
Keywords: THERMAL-OXIDATION; SILICON; STRESS; FIELD